Klimagebundene Risikostufen der Ertragsbildung und räumliche Standortdifferenzierung der Landwirtschaft im Maghreb - Achenbach, Hermann (ERDKUNDE, 1979)
Form and intensity of soil utilisation in the Maghreb depends to a decisive degree on the hygric variability. Not only the irregularities of the annual precipitation volume, but equally the monthly fluctuations of the hygric supply are significant for agriculture. In order to arrive at a quantitative recording of the monthly variability the monthly percentages of hygric size-classes were calculated for selected Tunisian stations for a period of fifty years. The frequency of the long term monthly precipitation supply thus established is presented in Fig. 2. It appears that the reliability of precipitation within the vegetative period is responsible for four types of soil utilisation : 1. The type of Mediterranean poly culture with crop rotation and permanent utilisation. 2. The type of cereal cultivation in a biennial rhythm with a short intermediate crop in winter. 3. The type of exclusive extensive biennial cereal culture (dry farming) and 4. The type of extensive tree cultivation in connection with specific cultivation techniques.